UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM PENGGUNAAN MEDIA TIK MELALUI KEGIATAN WORKSHOP DI SMPN 2 TELUK KUANTANKECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Rifdan Rifdan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is motivated by the weakness of teachers in the use of information and communication technology(ICT) media in the teaching and learning process. This research was conducted at SMPN 2 Teluk Kuantan. Thisstudy uses a school action research design consisting of 2 cycles. Each cycle consists of 4 stages, namely,planning, implementation, observation and reflection. From the results of the first cycle research, indicators ofteacher attendance, from 39 teachers, 30 or 76.92% of teachers attended, in cycle II it increased to 39 teachersor 100%. Leptop readiness indicator, 20 or 51.28% of teachers are in the ready category, in the second cyclebecomes 77 or 94.87%. Indicators of physical and mental readiness, 26 or 66.66% of teachers categorized asready, in cycle II to be 39 or 100%. Judging from the observations of teachers in the use of ICT as a medium ofteaching, in cycle I, word processing indicators scored 65 or 55.55% in the sufficient category, the second cycleincreased to 101 or 86.32% in the very good category. Indicators process spreadsheets and graphics, in the firstcycle 74 or 63.24% in the good category, in the second cycle it becomes 103 or 88.03% in the very goodcategory. Indicators of making interactive presentations using power points, 69 cycles or 58.97% are sufficientcategories, cycle II becomes 110 or 94.01% with very good categories. It can be concluded that theimplementation of ICT workshops can improve the ability of teachers in the use of ICT as a teaching medium atSMPN 2 Teluk Kuantan.